Experience in a public hospital with the use of cortical bone grafts of olecranon for the treatment of bone gaps in the hand - Pacheco-Lopez, Ricardo Cesar; Garcia-Gonzalez, Ivan Alejandro; Rendon-Medina, Marco Aurelio (International Journal of Research in Medical Sciences, 2022)
Background: Bone grafting has been a popular approach for the reconstruction of hand bone abnormalities caused by trauma or tumor removal. Cortical bone grafts have mostly osteoinductive capabilities. Olecranon grafts are reported to be safe because of their low donor morbidity and appropriate quick mechanical stability. Methods: This was a longitudinal descriptive study where 23 patients with hand fractures who were reconstructed with olecranon bone graft were evaluated. We included patients who were admitted to surgery at the “General Dr. Rubén Lenero” Hospital between January 2019 and November 2021. After surgery, a control radiograph of the graft insertion location and the donor area was taken postoperatively. Results: A post-surgery control elbow X-ray did not show any fracture data in all patients. The olecranon graft widths of the 23 patients ranged from 5 mm to 12 mm, with an average width of 7.9 mm. The lengths of the olecranon grafts ranged from 5 mm to 47 mm, with an average length of 19.62 mm. Conclusions: In this study, we found that cortical olecranon grafts have been a safe and viable reconstructive choice for our center for bone gap reconstruction in hand.